2006
DOI: 10.1002/masy.200651324
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Observations of Grain Boundary Morphologies in a Cylinder‐Forming Block Copolymer

Abstract: Summary:The grain boundary morphology of a cylinder-forming poly(styreneblockisoprene) (SI) diblock copolymer was investigated using transmission electron microtomography (TEMT). The three-dimensional (3D) morphologies of the grain boundaries between the two grains with different orientation angle, a, were investigated. In the present study, two kinds of grain boundary morphologies, a ' 908 and a ' 1208, were examined in 3D. It was found that, in the case of a ' 908, most of the cylindrical domains bent at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…For example, Jinnai et al found that the tortuosity and continuity of domains in a cylinder‐forming sample were strongly affected by the grain orientation angle (Fig. 9) . When the inter‐grain orientation angle was ∼90°, the majority of the cylindrical domains bent at the grain boundary to avoid intersecting each other (i.e., the domains were discontinuous).…”
Section: Block Copolymer Electrolytes For Solid‐state Lithium Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Jinnai et al found that the tortuosity and continuity of domains in a cylinder‐forming sample were strongly affected by the grain orientation angle (Fig. 9) . When the inter‐grain orientation angle was ∼90°, the majority of the cylindrical domains bent at the grain boundary to avoid intersecting each other (i.e., the domains were discontinuous).…”
Section: Block Copolymer Electrolytes For Solid‐state Lithium Batteriesmentioning
confidence: 99%
“…9). 106 When the inter-grain orientation angle was 90 , the majority of the cylindrical domains bent at the grain boundary to avoid intersecting each other (i.e., the domains were discontinuous). Furthermore, the reduction of cross-sectional area of conducting channels (i.e., decrease in conductivity) could be found at grain boundaries in lamellaeforming samples (Fig.…”
Section: Morphology Effectsmentioning
confidence: 99%
“…Alignment of PEO cylinders within the channel is likely a combination of confinement effects imposed by the channel side-wall [22] coupled with 'registry' of previously aligned domains on the crests [18]. This 'registry' mechanism maintains the hexagonal packing of the PEO cylinders while reducing the overall number of energetically unfavourable grain boundaries [23]. However, this alignment only extends for distances of ca.…”
Section: Graphoepitaxy Of Ps-b-peo/psmentioning
confidence: 99%
“…In the previous works, various heterogeneous structures have been observed by FIB-SEM and electron tomography: that is, island-sea, cylinder, gyroid and lamellar structures for block and graft copolymers [1,2] as well as dispersion of primary nanoparticles, structure of secondary aggregates, and 3D filler-network structure for filled polymers [1,2,[6][7][8]. Some important findings were achieved by 3D observations through FIB-SEM and electron tomography.…”
Section: Introductionmentioning
confidence: 97%
“…The analytical technique may be required to evolve in observation of morphology through not only tomography technique of electron and X-ray but also compatible technique in order to enhance precision and accuracy. In fact, in the last decade, grain boundary and structural defects of the nanostructure were investigated by 3D imaging techniques [1,2]. We could be able to relate the properties to distortion of the nanostructure with load force if we had combined a fabrication technique of the anisotropic structure.…”
Section: Introductionmentioning
confidence: 99%